Correlation of fear memory in a PTSD animal model and hippocampal BDNF in response to β-estradiol treatment - Saffari, Shaghayegh; Abrari, Kataneh; Rezaei, Arezu; Rashidy-Pour, Ali; Goudarzi, Iran; Elahdadi Salmani, Mahmoud (Archives of Advances in Biosciences, 2015)
The most important characteristics of PTSD, as an anxiety disorder, are memory disorders and hippocampus is one of the essential structures which plays a critical role in PTSD memory disorders. Traumatic events cause apoptosis and alter the expression of neurotrophic factors in hippocampus. The aim of this study is to evaluate the effects of β-Estradiol on behavioral responses in PTSD and to study its biochemical and histological mechanisms. We used single prolonged stress (SPS) to develop PTSD in rats. The day after, the rats received electrical foot shock within shock chamber. One week later, in order to test the conditioned fear responses, the freezing behavior of rats were examined for 5 continuous days, as they were placed back in the chamber without any shock. Animals received multiple injections of β-estradiol or sesame oil, immediately after shock and also on a daily basis through the seven days prior to the test. Hippocampal cell count was implemented after cresyl violet staining. We measured BDNF protein levels by ELISA kit. Main findings of this study confirmed that exaggerated fear response is observed in PTSD group as compared with control group and β-estradiol administration reduced these exaggerated behavioral responses. We found out that SPS decreases the density of cells in hippocampus and this effect is partly corrected by β-estradiol; β-estradiol increased BDNF protein level in hippocampus as compared with PTSD group; BDNF protein level was negatively correlated with freezing response in both SPS+β-estradiol and SPS+sesame group.The results of this study is consistent with the hypothesis that decreased expression of BDNF contributes to memory impairment in PTSD and up regulation of BDNF by β-estradiol plays a role in memory treatment.